Bioresponse Inspired Nanomaterials for Targeted Drug and Gene Delivery - Sharma, Shrestha; Javed, Md. N.; Pottoo, Faheem Hyder; Rabbani, Syed Arman; Barkat, Md. Abul; Harshita; Sarafroz, Md.; Amir, Mohd. (Pharmaceutical Nanotechnology, 2019)
The traditional drug delivery techniques are unresponsive to the altering metabolic states of the body and fail to achieve target specific drug delivery, which results in toxic plasma concentrations. In order to harmonize the drug release profiles, diverse biological and pathological pathways and factors involved have been studied and consequently, nanomaterials and nanostructures are engineered in a manner so that they respond and interact with the target cells and tissues in a controlled manner to induce promising pharmacological responses with least undesirable effects. The bioinspired nanoparticles such as carbon nanotubes, metallic nanoparticles, and quantum dots sense the localized host environment for diagnosis and treatment of pathological states. These biocompatible polymeric- based nanostructures bind drugs to the specific receptors, which renders them as ideal vehicles for the delivery of drugs and gene. The ultimate goal of bioinspired nanocomposites is to achieve personalized diagnostic and therapeutic outcomes. This review briefly discussed current trends; role, recent advancements as well as different approaches, which are being used for designing and fabrication of some bioinspired nanocarriers.
Keywords: Bioinspired nanocarriers